Evidence of 3D strain gradients associated with tin whisker growth. (February 2018) - Hektor, Johan; Marijon, Jean-Baptiste; Ristinmaa, Matti; Hall, Stephen A.; Hallberg, Håkan; Iyengar, Srinivasan; Micha, Jean-Sébastien; Robach, Odile; Grennerat, Fanny; Castelnau, Olivier
Abstract: We have used Differential Aperture X-ray Microscopy (DAXM) to measure grain orientations and deviatoric elastic strains in 3D around a tin whisker. The results show strain gradients through the depth of the tin coating, revealing a higher strain deeper in the Sn layer. These higher strains are explained by the volume change occurring during growth of the intermetallic phase Cu6 Sn5 at the interface between the Cu substrate and the Sn coating and at grain boundaries between Sn grains. Graphical abstract: